KONSEP KETATANEGARAAN DALAM ISLAM - Herawati, Andi (DIKTUM: Jurnal Syariah dan Hukum, 2013)
Quran as scripture has laid the principles and ethical values ââin society and state. The principles practiced by the Prophet in his capacity as head of state, so he was able to create a system of government that is peaceful, prosperous and democratic. Government that upholds justice, equality, and protection of human rights